Multinational Firms and Business Cycle Transmission - Dominik Menno (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
This paper studies the effect of foreign direct investment (FDI) on the transmission of international business cycles. I document for the G7 countries between 1991 and 2006 that increases in bilateral FDI linkages are associated with more synchronized investment cycles. I also find that the relation between FDI integration and synchronization of gross domestic product (GDP) is - yet positive - statistically insignificant after controlling for time fixed effects. I then study a model of international business cycles with an essential role for FDI and shocks to multinational activity. In the model, more FDI openness unambiguously increases investment synchronization while the effect on GDP synchronization is ambivalent. Due to mismeasurement of intangible capital in national accounts, the actual elasticity of output synchronization with respect to FDI integration is underestimated. The effects measured in the data are quantitatively consistent with the model predictions. Finally, I show that more FDI increases households' welfare by reducing aggregate risk on the production side; this effect,however, is partially mitigated by multinational specific shocks.
Keywords: E32; F23; F44; 330